2018
DOI: 10.5530/ijper.52.4s.86
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro Study of Cytotoxic Activity of Euphorbia macroclada boiss on Mcf–7 Cells

Abstract: Objective: The study was aimed to evaluate the cytotoxic activity of acetone extract of leaves, flower and body of Euphorbia macroclada boiss on human breast cancer cell line (MCF-7). Material: The cells were plated at a cell density of 1x10 5 cells in 96-well plates and grown with DMEM medium containing supplemented with 10% FBS and 1% penicillin. The cells were treated by different concentrations of acetone extract of Euphorbia macroclada boiss (10-1000 µg/mL) during 24, 48 and 72 h. The cytotoxic activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It was previously reported that E. hirta methanolic extract significantly inhibited the proliferation of MCF-7 cells at 24 h at the GI 50 value of 25.26 µg/mL [32], much lower than that of E. bicolor latex extract in our study. Acetone extracts of E. macroclada leaves and flowers induced significant cytotoxicity in MCF-7 breast carcinoma [33]. Butanol, hexane or methanol extracts of E. tirucalli stem inhibited the proliferation of MCF-7 and MDA-MB-231 in a concentration dependent manner [19].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that E. hirta methanolic extract significantly inhibited the proliferation of MCF-7 cells at 24 h at the GI 50 value of 25.26 µg/mL [32], much lower than that of E. bicolor latex extract in our study. Acetone extracts of E. macroclada leaves and flowers induced significant cytotoxicity in MCF-7 breast carcinoma [33]. Butanol, hexane or methanol extracts of E. tirucalli stem inhibited the proliferation of MCF-7 and MDA-MB-231 in a concentration dependent manner [19].…”
Section: Discussionmentioning
confidence: 99%